A Scoping Review of Practitioner Research on Sensitive Topics - Håvard Haugstvedt (Nordic Journal of Social Research)
Practitioner research, which involves professionals such as social workers, educators, and nurses, is an approach that may help establish contact with hard-to-reach targets while also exposing the researcher to potentially sensitive and ethically challenging situations and dilemmas. Through a scoping review of the scholarly literature, this paper explores evidence of the effects that research on sensitive topics may have on the researcher and how the researcher can prepare for this. Twenty-four peer-reviewed articles were analysed using thematic analysis, which provided the following four themes: researcher competency, researcher vulnerability, researcher role, and participant vulnerability. In addition, peer support, formal support measures, and research and time management were found to potentially counteract the adverse effects of conducting qualitative research on sensitive topics. The findings of this scoping review strongly suggest that practitioner researchers investigating sensitive issues should partner with professional research institutions from the beginning of the research process to end. In addition, strengthening the research methodology used during the bachelor’s degree educations of professionals such as social workers might help to develop more resilient practitioner researchers. This must, however, be weighed against other necessary courses.